Effects of sanitation and hygiene perceptions on international travelers' health, travel plans and trip experiences in India - Chandra, Rishita; Supehia, Sakshi; Nath, Bhola; Chhetri, Charu; Kumari, Ranjeeta; Joshi, Kumari Damayanti; Sharma, Roshan; Chaudary, Jatin; Joshi, Kishor; Bhatta, Ramesh; Bhatt, Chhavi R. (Frontiers in Public Health, 2022)
Background: International travellers often experience travellers’ diarrhoea. However, there is paucity of data on whether self-reported gastrointestinal symptoms influence travellers’ perceptions of adequacy of sanitation and hygiene services encountered during travel, and to what degree their travel plans, and overall trip experience are impacted. Methods: A cross-sectional face-to-face survey was conducted amongst international travellers in India. Data collected included socio-demographics, travel characteristics, self-reported occurrence and frequency/severity of gastrointestinal symptoms, perceptions of sanitation and hygiene encountered, and adverse effects of symptoms on travel plans and trip experiences. Chi-square tests and logistic regression were performed to describe differences and associations between categorical variables. Results: Of the 300 international travellers surveyed, 46.3% experienced diarrhoea. At least two-thirds of travellers perceived the quality of sanitation (67.0%) and hygiene (70.0%) encountered to be inadequate. Perceptions of inadequate sanitation (adjusted OR=3.0; 95% CI 1.7-5.5) and poor hygiene (adjusted OR=7.7; 95% CI 4.1-15.5) were higher among travellers who experienced diarrhoea. Additionally, both higher likelihood of travel plans being affected (adjusted OR=10.7; 95% CI 5.1-23.6) and adverse impacts on overall trip experience (adjusted OR=2.8; 95% CI 1.4-5.8) were reported among those who experienced diarrhoea. Conclusions: More than two thirds of travellers surveyed in India experienced inadequate sanitation and hygiene services, with perceptions influenced by occurrence and frequency of diarrhoea. Self-reported diarrhoea was also associated with adverse effects on travel plans and overall trip experience. While these results may seem intuitive, they have important implications and suggest that improving sanitation and hygiene standards in India could potentially enhance tourism.